Minimally invasive determination of pancreatic ductal adenocarcinoma (PDAC) subtype by means of circulating cell‐free RNA - Martin Metzenmacher; Gregor Zaun; Marija Trajkovic‐Arsic; Phyllis Cheung; Timm M. Reissig; Hendrik Schürmann; Nils vonNeuhoff; Grainne O'Kane; Stephanie Ramotar; Anna Dodd; Steven Gallinger; Alexander Muckenhuber; et al. (Molecular Oncology)
Pancreatic ductal adenocarcinoma (PDAC) comprises two clinically relevant molecular subtypes that are currently determined using tissue biopsies, which are spatially biased and highly invasive. We used whole transcriptome sequencing of 10 plasma samples with tumor‐informed subtypes, complemented by proteomic analysis for minimally invasive identification of PDAC subtype markers. Data were validated in independent large cohorts and correlated with treatment response and patient outcome. Differential transcript abundance analyses revealed 32 subtype‐specific, protein‐coding cell‐free RNA (cfRNA) transcripts. The subtype specificity of these transcripts was validated in two independent tissue cohorts comprising 195 and 250 cases, respectively. Three disease‐relevant cfRNA‐defined subtype markers (DEGS1, KDELC1, and RPL23AP7) that consistently associated with basal‐like tumors across all cohorts were identified. In both tumor and liquid biopsies, the overexpression of these markers correlated with poor survival. Moreover, elevated levels of the identified markers were linked to a poor response to systemic therapy and early relapse in resected patients. Our data indicate clinical applicability of cfRNA markers in determining tumor subtypes and monitoring disease recurrence.